2011
DOI: 10.1258/mi.2011.011001
|View full text |Cite
|
Sign up to set email alerts
|

Short-term estrogen replacement therapy reduces platelet marker levels in Malaysian postmenopausal women

Abstract: Short-term ERT leads to reduction in platelet activity, which might contribute to protection against cardiovascular diseases in healthy PMW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although the relationships of different hypertension subtypes with age and sex are controversial, a considerable number of studies [ 5 , 33 , 35 , 29 ] agree with the view that being female and being old play pivotal roles in the development of ISH. Another study [ 42 ] from Sheikh et al showed that platelet activation decreased after hormone replacement therapy among postmenopausal women. Our data showed that the prevalence of ISH exceeded half of the population of individuals over 60 years for the first time in females, and the mean age of women with ISH was 63.15 years, which was older than the usual menopause age.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationships of different hypertension subtypes with age and sex are controversial, a considerable number of studies [ 5 , 33 , 35 , 29 ] agree with the view that being female and being old play pivotal roles in the development of ISH. Another study [ 42 ] from Sheikh et al showed that platelet activation decreased after hormone replacement therapy among postmenopausal women. Our data showed that the prevalence of ISH exceeded half of the population of individuals over 60 years for the first time in females, and the mean age of women with ISH was 63.15 years, which was older than the usual menopause age.…”
Section: Discussionmentioning
confidence: 99%